Factory-Made Elastic Silicone Sheet as an Alternative for the Posterior Capsule of the Lens During Phacoemulsification for Dislocated/Subluxated Lenses - Akamine R (Dove Medical Press, 2021)
Rinko Akamine, Naomi Miyamoto, Shoko Kiritoshi, Mami Kusaka, Masayuki Akimoto Osaka Red Cross Hospital, Osaka, JapanCorrespondence: Masayuki AkimotoOsaka Red Cross Hospital, 5-30 Fudegasakicho, Tennojiku, Osaka, 543-8555, JapanEmail masayuki@akimoto3.comBackground: We previously reported a novel technique using an elastic silicone bowl, which was handmade from a phaco test chamber, to salvage dislocated lenses and perform phacoemulsification and aspiration (PEA) on the bowl. However, creating the bowl was challenging.Methods: A factory-made elastic silicone sheet (ESS), a ready-to-use alternative for the posterior capsule of the lens, was prepared. We used this sheet to salvage and support the dislocated/subluxated lenses in 11 eyes of nine patients.Results: We could use a sheet immediately after we opened the package. In all the cases, we could insert a sheet beneath the lens and PEA performed at the center of the operative field. There was only one incident where the lens could not be placed onto the disc at the first attempt, but the lens was eventually salvaged. There was no risk of rupture during PEA, and the ESS could be removed completely without any complications.Conclusion: The factory-made ESS described here can be used for salvaging dislocated/subluxated lenses and safely performing PEA.Keywords: lens dislocation, perfluorocarbon, alternative posterior capsule of the lens